A Mitochondria‐Targeting Gold–Peptide Nanoassembly for Enhanced Cancer‐Cell Killing. Issue 12 (8th May 2013) - Ma, Xiaochuan; Wang, Xiaobo; Zhou, Ming; Fei, Hao
Abstract Design and construction of multifunctional nanoparticles for effective delivery and therapeutic application remains a challenging task. It is desirable that nanoparticles can overcome multiple biological barriers and reach specific cellular locations to achieve maximum therapeutic effects. This aim often requires the fine tuning of nanoparticles' chemical and physical properties, as well as better understanding of their interaction with live cells. A peptide‐modified gold–nanoparticle platform is designed, which consists of a 20‐nm gold core stabilized with a layer of biotinylated CALNN‐based peptides and a further layer of tetrameric streptavidins for functionalization with biotinylated molecules. The nanoassembly undergoes an efficient dynamin‐dependent and caveolae‐mediated endocytosis pathway, and displays highly specific localization to mitochondria, organelles of great therapeutic importance. When functionalized with a cytotoxic peptide (KLA: (KLAKLAK)2), the KLA‐anchored nanoassembly exhibits dramatically enhanced anticancer activity, thousands of times stronger than that of the free KLA peptide, likely because of its improved cell entry efficiency, mitochondria‐specific delivery, and the polyvalent effect of the nanoassembly. The study opens up the possibility of developing mitochondria‐targeted nanomedicines.